Heating and cooling load calculations - Down, P. G. (International series of monographs in heating, ventilation, and refrigeration, 1969)
Heating and Cooling Load Calculations is a handbook that covers various concerns in calculating heating and cooling. The title provides a logical study of the physical and engineering factors that affect the heating and cooling load.